Palladium-Catalyzed Heteroannulation Approach to 1,2-Bis(3-indolyl)ethanes - Blair, Lachlan M.; Sperry, Jonathan (Synlett, 2013)
Palladium-catalyzed heteroannulation between indole-3-butanal and various o-iodoanilines provides a straightforward synthesis of 1,2-bis(3-indolyl)ethanes, which are useful precursors to valued indolo[2,3a]carbazoles. 1,2-Bis(3-indolyl)ethanes bearing a variety of substituents are available by using this methodology, with one transformed into the natural product 1,2-bis(3-indolyl)ethane-1,2-dione through a novel double Yonemitsu oxidation.
Keywords: indole; heteroannulation; indole derivatives; palladium; natural products